Synthesis and Applications of Asymmetric Catalysis Using Chiral Ligands Containing Quinoline Motifs - Vasudevan Dhayalan; Rambabu Dandela; K. Bavya Devi; Ragupathy Dhanusuraman (SynOpen, 2022)
In the past decade, asymmetric synthesis of chiral ligands containing quinoline motifs, a family of natural products displaying a broad range of structural diversity and their metal complexes, have become the most significant methodology for the generation of enantiomerically pure compounds of biological and pharmaceutical interest. This review provides comprehensive insight on the plethora of nitrogen-based chiral ligands containing quinoline motifs and organocatalysts used in asymmetric synthesis. However, it is confined to the synthesis of quinoline-based chiral ligands and metal complexes, and their applications in asymmetric synthesis as homogeneous and heterogeneous catalysts. 1 Introduction 2 Synthesis of Chiral Ligands Containing Quinoline Motifs 2.1 Synthesis of Schiff Base Type Chiral Ligands 2.2 Synthesis of Oxazolinyl-Type Chiral Ligands 2.3 Synthesis of Chiral N,N-Type Ligands 2.4 Synthesis of Amine-Based Chiral Ligands 2.5 Synthesis of P,N-Type Chiral Ligands 2.6 Synthesis of Chiral N-Oxide and Nitrogen Ligands 3 Homogeneous Catalytic Asymmetric Reactions 3.1 Asymmetric Carbon–Carbon Bond Formation Reactions 3.2 Asymmetric Allylic Reactions 3.3 Asymmetric Cycloadditions 3.4 Asymmetric Carbene Insertions 3.5 Asymmetric Pinacol Couplings 3.6 Asymmetric Pudovik Reactions 3.7 Asymmetric Strecker Reactions 4 Heterogeneous Catalytic Asymmetric Reactions 4.1 Asymmetric Cyclopropanation of Olefins 4.2 Asymmetric Heck Reactions 4.3 Asymmetric Hydrogenations 4.4 Asymmetric Hydroformylation of Styrene 4.5 Asymmetric Dialkoxylation of 2-Propenylphenols 4.6 Asymmetric Cascade Cyclizations 4.7 Asymmetric Allylic Alkylations 4.8 Asymmetric Alkylation of β-Keto Esters 4.9 Asymmetric C–H Bond Arylation Reactions 4.10 Intramolecular Aerobic Oxidative Amination of Alkenes 4.11 Asymmetric Oxidative Hydroboration of Alkenes 5 Conclusions